Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2017-2021 - Siti Nur Qomariyah; Nur Aidah Fitriana (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to examine the influence of Corporate Social Responsibility (CSR) on financial performance. Financial performance is an analysis used to see how well a company has worked by using correct and appropriate financial performance rules. In this research, the company's financial performance is measured using Return On Assets (ROA), Return On Equity (ROE), and Return On Sales (ROS). Corporate Social Responsibility (CSR) as the independent variable and Return On Assets (ROA), Return On Equity (ROE), and Return On Sales (ROS) as the dependent variable. This type of research is quantitative research using a purposive sampling method. So a sample of 37 basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period can be obtained. The analytical method used in this research is simple regression analysis. The research results show that Corporate Social Responsibility (CSR) has a positive effect on Return On Assets (ROA), Corporate Social Responsibility (CSR) has a positive effect on Return On Equity (ROE), and Corporate Social Responsibility (CSR) has a positive effect on Return On Sales ( ROS).